PENGARUH PUPUK LIMBAH CINCAU TERHADAP PENYAKIT DAN KEANEKARAGAMAN SERANGGA TANAMAN JAGUNG - imam Habibi; setyawan, Fajar; Listiawati, Selia; Cholil Mahfud, Mohammad (Universitas Islam Balitar, 2023)
Utilization of organic fertilizer aims to increase soil fertility and efforts to improve the balance of the corn plant ecosystem. One source of organic fertilizer is black grass jelly waste, both solid and liquid. Black grasss jelly waste is available in excess because factories that produce black grass jelly have not utilized the waste as an alternative to organic fertilizer. The purpose of this study was to determine the effect of organic fertilizer from black grass jelly waste both solid and liquid on the abundance of insects and their natural enemies. This research started from September to December 2021. It took place at the Integrated Field Laboratory, Kadiri Islamic University, in Rejomulyo Village, Kediri City, with a pH of 7, daily temperature and humidity (±28.3°C and 72.2%) with rainfall 45 mm/month. Variable observations of downy mildew disease sentitivity index and insect diversity. The results showed that the effect of grass jelly fertilizer had an effect on the level of resistance to downy mildew attacks. In all the insects found were 47 families consisting of 6 orders. On diversity has a moderate value. In terms of evenness and species richness, it was found that all the results had high scores. So that the treatment of solid and liquid fertilizers against insect diversity is very good.